Numerical study on the effect of protective wall depth in reducing structure deformations caused by tunnelling. (June 2023) - Song, Geyang; Xu, Jingmin; Marshall, Alec M.
Abstract: To reduce tunnelling induced damage of buildings, a 'protective wall' is sometimes constructed between the location of the new tunnel and existing foundations. One of the key design questions relates to the optimal wall depth, where further increase has a limited benefit in reducing structural distortions. This paper presents the results from finite element analyses used to study how protective walls reduce tunnelling induced damage to adjacent structures. A scenario where the protective is located very close to a tunnel is studied, which is considered to be of practical interest and a critical case concerning potential for building damage. The analyses consider a tunnel with a row of 4 piles (in sand) supporting a 5-storey steel frame running transverse to the tunnel direction, with a wall located between the tunnel and the first pile. Results show that the protective wall's depth affects soil and pile settlements, the redistribution of loads applied to the piles (due to structure stiffness), and ultimately structural deformations and building damage. For the case considered, the optimal depth of the wall is approximately 1.25 times the tunnel axis depth; marginal reductions in pile settlements and building damage are obtained as wall depth is increased further.